Pro-oxidant and lifespan extension effects of caffeine and related methylxanthines in caenorhabditis elegans - Li, Hanmei; Roxo, Mariana; Cheng, Xinlai; Zhang, Shaoxiong; Cheng, Haoran; Wink, Michael (Food chemistry: X, 2019)
Caffeine and related purine alkaloids are common ingredients of many stimulating drinks. Studies have shown that lower concentrations of caffeine have a protective role in aging-related disorders. However, the associated mode of action of caffeine and its related methylxanthines is still not clear. In this study, we demonstrated that caffeine and theophylline promote longevity in Caenorhabditis elegans. Lifespan studies with the wild type, DAF-16 and SKN-1 mutant strains indicated that the methylxanthines-mediated lifespan extension in C. elegans was independent of DAF-16/FOXO and SKN-1. All the tested methylxanthines could protect C. elegans against acute oxidative stress. At early stages of life, an increase of ROS (reactive oxygen species) induced the translocation of DAF-16 and SKN-1, resulting in upregulation of several antioxidant genes, for example, sod-3p::GFP, gst-4p::GFP, gcs-1p::GFP; and downregulation of hsp-16.2p::GFP. RT-PCR corroborates the upregulation of gst-4 and skn-1 genes. The expression of DAF-16 decreased although its nuclear translocation was induced.
Gesehen am 09.10.2020